Isolasi Nanoselulosa Terkarboksilasi dari Limbah Kulit Pisang Ambon Lumut dengan Metode Oksidasi - Ashari Budi Nugraha; Ahmad Nuruddin; Bambang Sunendar (Journal of Science and Applicative Technology, 2021)
In this study, banana peel from ambon lumut (Musa acuminata) was used as source for nanocellulose fibers. Carboxylated nanocellulose was isolated with oxidation method using ammonium persulfate (APS). In order to investigate the effect of temperature towards the characteristics of nonocellulose, temperature for oxidation process was set at three different values: 60 °C, 70 °C, dan 80 °C. Nanostructure of cellulose was observed as a mix of fibers and whiskers from transmission electron microscopy (TEM) images. The diameter of nanocellulose is ranging from 12,1 to 25,1 nm. Data from spectrometry graphs (FTIR) confirms the existence of carboxyl functional groups in nanocellulose samples. X-ray diffraction pattern (XRD) shows that crystallinity index values increase as temperature of oxidation process increases. The highest crytallinity index value of 72,4% was obtained from nanocellulose treated with oxidation temperature of 80 °C. This analysis shows banana peel waste as a potential alternative source for carboxylated nanocellulose.